Emerging trends and research foci of berberine on tumor from 2002 to 2021: A bibliometric article of the literature from WoSCC - Yuan, Runzhu; Tan, Yao; Sun, Ping-Hui; Qin, Bo; Liang, Zhen (Frontiers in Pharmacology, 2023)
Background: Cancer, also known as Malignant Tumor, is caused by the activation of oncogene, which leads to uncontrolled proliferation of cells, thus forming swelling. The World Health Organization (WHO) noted that one of the main causes of death worldwide is cancer, which poses a grave threat to the safety and health of people. The main variables limiting of anti-tumor treatment efficacy, nevertheless, are side effects and drug resistance. The hunt for natural, safe, low toxicity and efficient chemical compound in tumor research is essential. Berberine is a pentacyclic isoquinoline quaternary ammonium alkaloid isolated from Berberis and Coptis. It has long been utilized in clinical settings. In recent years, there are many literature reports that berberine has also been used for cancer treatments. The development of future research for researchers is made possible by bibliometric analysis, a scientific and quantitative method for evaluating the published papers. It assists researchers in identifying the development patterns and research hotspot of a certain study topic. Materials and methods: We draft this study using research articles from the Web of Science Core Collection (WOSCC) of Clarivate Analytics from January 1, 2002 to December 31, 2021. Using Microsoft Excel software, CiteSpace, Vosviewer, and an online platform for literary metrology analysis. Results: There were a total of 1368 publications which had unique characteristic in the end. Publications from China were the most in number with 783 articles. Feng, Y.B, coming from China, was the most productive authors and received the highest total citations. China Medical University (Taiwan) and Sun Yat-Sen University were the two organizations with the largest number of documents in parallel,36. The most publications were published in Frontiers in Pharmacology, which had 29 in total. The present body of research is focused on the mechanism, molecular docking," and "oxidative stress" of berberine on tumors. Conclusions: The research on berberine and tumor was thoroughly reviewed utilizing knowledge-map and bibliometric methods. The current study helps researchers better understand the dynamic evolution of berberine and tumor, and it provides a direction for the research of BBR on the treatment of tumors in future research